If a , b , c are all positive , a + b + c = 1 and ( 1 − a ) ( 1 − b ) ( 1 − c ) is greater or equal to K × a b c , find K .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
reverse rearrangement inequality would have been a faster approach. nice solution anyways!.(+1)
I did same. (+1)
this can be written as: ( a + b ) ( b + c ) ( c + a ) WLOG, a≥b≥c. we have the sets (a,b,c) and (a,b,c). by reverse rearrangement inequality this is "random sum≥direct sum" ( a + b ) ( b + c ) ( c + a ) ≥ ( a + a ) ( b + b ) ( c + c ) = 8 a b c (equality achieved at a = b = c = 3 1 .)
We can rewrite the given expression as ( a + b ) ( b + c ) ( c + a ) ≥ 2 a b × 2 b c × 2 c a , by A.M-G.M inequality = 8 a b c ⟹ k = 8 . Equality occurs at a = b = c = 3 1 .And done!
Problem Loading...
Note Loading...
Set Loading...
Expanding and simplifying, we find that
( 1 − a ) ( 1 − b ) ( 1 − c ) = ( 1 − a − b + a b ) ( 1 − c ) =
1 − a − b + a b − c + a c + b c + a b − a b c = a b + a c + b c − a b c
since a + b + c = 1 . Now since a , b , c are all positive, a b , a c , b c will be as well. So by the AM-GM inequality we find that a + b + c ≥ 3 ( a b c ) 3 1 and that a b + a c + b c ≥ 3 ( a b c ) 3 2 .
Multiplying these two inequalities, we see that
( a + b + c ) ( a b + a c + b c ) ≥ 9 a b c ⟹ a b + a c + b c ≥ 9 a b c
since a + b + c = 1 . Thus
( 1 − a ) ( 1 − b ) ( 1 − c ) = a b + a c + b c − a b c ≥ 9 a b c − a b c = 8 a b c , and so K = 8 .
(Note that equality holds when a = b = c = 3 1 .)